Strategy of Islamic Rural Banks Improving Financial Performance During the Covid-19 Pandemic - Mardhiyaturrositaningsih, Mardhiyaturrositaningsih; Janah, Rohmatul (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
This study aims to measure the pattern of Islamic Rural Banks strategic management in Central Java during the Covid-19 Pandemic. This study use SWOT Analysis by determining Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS). The sources of this research data were collected through a Focus Group Discussion conducted with the Financial Services Authority, Islamic Rural Banks Practitioners and Academics. The results of the study show that the Islamic Rural Banks considers the Covid-19 pandemic as a challenge with several priority aspects of control. Strategy formulation and implementation are carried out through changes to the Bank's Business Plan. Bank limited the distribution of high-risk financing during the Covid-19 Pandemic. Islamic Rural Banks focuses on the health sector, cooperation and government projects.